Sustainable Harvest of Medicinal Plants: an Initiative in Southern India - Thomas, Winfred D.; Ganesh Babu, N. M.; Ghate, Utkarsh; Ravikumar, K. (Indian Forester, 2005)
Urbanisation and scientific rediscovery is increasing the demand for herbal products, whose overharvest threatens 30% of the traded species. Sustainable harvest traditions are eroding due to (a) poor prices paid to the raw drug gatherers, (b) competition between, (c) market insecurity, (d) many youth gatherers and (e) vehicular mobility to new collection areas. To revive traditions through equitable benefit sharing, Gram Mooligai (i.e. Village Herbs) Company Limited (GMCL) was established, with gatherer's groups as shareholders in Tamil Nadu state in Southern India. Sustainable Biometric experiments could not continue or help in predicting yield but participant observations and "memory harvesting" revealed that focal species have become rare amongst 25% of their earlier collection areas. Major pressures other than harvest indude (a) scarce or untimely rainfall, (b) habitat encroachments and (c) grazing. To earn more better price and sustained business demand, GMCL gatberers maximised not quantity but quality tbrougb tbumb rules ("do's and don'ts") of sustainable barvesting practices: (a) appropriate babitat area (b) maturity timing (c) less damaging methods (d) proper post-harvest treatment (e) user (buyer, co-harvester) agreements.